2018
DOI: 10.3390/app8122467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Connection Type between Surface Vessel and Submersible Propeller on Motion Performance of Wave Glider

Abstract: Wave Glider is an autonomous surface vehicle that directly uses wave energy to generate forward power and has been widely used in marine survey and observation. Wave Glider is composed of surface vessel, submersible propeller and the connection structure between them. Connection types are thought to be related to the performance of Wave Glider closely. In this paper, the effects of the connection structure between the surface vessel and the submersible propeller on the motion performance of the Wave Glider are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Feng P. Y .et al [14] established a frequency-domain coupled hydrodynamic model of oscillating fin and large cargo ship in the case of top wave, they analyzed the influence of fin on seakeeping of ship, and studied the influence of installation position of fin, spring stiffness, submergence depth and other parameters on wave energy recovery effect by using the model. Feng [15][16] established the multi-body dynamics model of unmanned vehicles.…”
Section: (D)-(e)) In 2008 Kenichimentioning
confidence: 99%
“…Feng P. Y .et al [14] established a frequency-domain coupled hydrodynamic model of oscillating fin and large cargo ship in the case of top wave, they analyzed the influence of fin on seakeeping of ship, and studied the influence of installation position of fin, spring stiffness, submergence depth and other parameters on wave energy recovery effect by using the model. Feng [15][16] established the multi-body dynamics model of unmanned vehicles.…”
Section: (D)-(e)) In 2008 Kenichimentioning
confidence: 99%
“…The two separate connection points must withstand occurring loads to avoid the glider breaking free from the surface unit. A study by [17] compared the types of tether connections between the sub and the surface unit. In the study, four separate connection types including rigid rod, cable, multi-link, and elastic rod were tested through modeling software.…”
Section: E Tethermentioning
confidence: 99%
“…Feng et al [8] established a cable model of a wave glider by considering the connection characteristics such as a rigid rod, cable, multi-link chain and elastic rod. The results showed that the propulsion performance with different connection types of the wave glider is slightly different.…”
Section: Introductionmentioning
confidence: 99%